Organic iso-type pentacene – lead phthalocyanine heterostructures - Vertsimakha, Ya.I.; Lutsyk, P.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The photovoltaic properties of organic iso-type heterostructures based on pentacene (Pn) and lead phthalocyanine (PbPc) prepared by thermal deposition at different substrate temperatures (Ts) are investigated. It is shown that, at modulated illumination for Pn/PbPc heterostructures prepared at Тs = 300 K, the reversal of a sign is observed in photovoltage spectra. The properties of the structures are well described by the Van Opdorp model that indicates the presence of the high surface recombination rate of charge carriers at the interface of heterostructure components. At this, the contribution of heterostructure components to the photovoltage formation can be changed with unmodulated monochromatic additional illumination. In Pn/PbPc heterostructures prepared at Ts = 370 K, there is no reversal of the photovoltage sign, and the photovoltage is significantly (up to twice) higher in comparison with both heterostructures obtained at Ts = 300 K and separate layers of components (Pn and PbPc). This is the evidence for the low recombination rate of charge carriers at the interface of Pn/PbPc heterostructures prepared at Ts = 370 K